REVIEW ON CHAKRADATTA - A GREAT TREATISE BY CHAKRAPANIDATTA - Chaudhari, *Tejaswini Govind; Sneha, Kubde; Mukund, Dive (International Journal of Ayurveda and Pharma Research, 2017)
Rasashastra (Indian Alchemy) forms the basis of Ayurvedic pharmaceutics. In ancient Ayurveda, the emphasis has been over the herbs and their therapeutic usages. Later on the animal products, metals and minerals started to find favor of the Ayurvedic practitioners. Ample of literature is available on Rasashastra. Chakradatta is one of the great treatise composed by Shri Chakrapanidatta, the well known Tikakarta of Charak Samhita. Chakradatta holds an important place amongst academicians, researchers and students of Rasashastra. Many verses of Chakradatta are derived from 50 sources. The principle source of this book as stated by the author himself at the end of the work is Vrndss Siddhayoga. Chakradattas main aim was to present it as an up to date text of Ayurveda medicine for the benefit of ailing mankind. The uniqueness of Chakradatta is in the description of several metallic and mercurial preparations for the purpose of internal use as medications. Therapeutic principles specific for the disease recommended by Chakradatta are beneficial even today for the practitioners of Ayurveda. Present paper will highlight the framework of Chakradatta, providing information about the author, text, characteristics & innovations. It will also throw a light towards the contribution of Chakradatta in the field of Ayurveda.